Technology Adoption in SMEs: Unraveling Bibliometric Patterns and Public Policy Influences - Dhabyan Khalid Rafasya; Jovandher Abraham Limbong; Shabrina Nailul Farich; Siti Salza Rahmadanita Nakhat; Chandika Mahendra Widaryo; Muhammad Ramadhani Kesuma (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rising dependence on digital technologies has made technology adoption a strategic requirement for SMEs aiming to enhance competitiveness and sustainability. However, adoption remains uneven, especially in developing economies where structural, behavioral, and policy factors shape digital transformation. This study analyzes bibliometric patterns and public policy influences in SME technology adoption research by examining Scopus-indexed publications (2010–2024) using VosViewer for keyword co-occurrence and co-authorship mapping. The results show that the literature centers on interconnected clusters, including technology adoption models, policy interventions, digital transformation, Industry 4.0, and data governance. Findings highlight the crucial role of public policy in supporting institutional readiness, infrastructure, and capacity building, while behavioral and organizational elements, such as managerial attitudes, perceived risks, and digital literacy, also affect adoption outcomes. Bibliometric trends reveal a shift from basic ICT tools to advanced digital ecosystems involving automation, AI, and cybersecurity. This mapping clarifies how policy and organizational dynamics jointly shape SME technology adoption and informs future research and policymaking.